THE ONLINE LABORATORY SIMULATION WITH CONCEPT MAPPING AND PROBLEM BASED LEARNING (OLS-CMPBL): IS IT EFFECTIVE IN IMPROVING STUDENTS’ DIGITAL LITERACY SKILLS? - Riki Perdana; Jumadi Jumadi; Dadan Rosana; Riwayani Riwayani (LPMPP Universitas Negeri Yogyakarta, 2020)
Digital literacy skills of students in Indonesia are still very low. This study aims to examining the effectiveness of Online Laboratory Simulation with Concept Mapping and Problem-Based Learning model in improving students’ digital literacy skills. The research objectives have been describing the significances of the difference between learned students using the PBL model, Online Laboratory Simulation with Problem-Based Learning (OLS-PBL) model, Online Laboratory Simulation with Concept Mapping and Problem-Based Learning (OLS-CMPBL) model. It is a quasi-experimental with pre and post-test design. The population of this research is students in Islamic State School Yogyakarta (MAN), Indonesia. The random sampling technique was used from the three schools of Islamic State Schools. There were 97 students of class XI science at Islamic State School 1 (MAN 1) as participant. The technique of data analysis was used the paired-sample t-test, comparative-descriptive analysis, and ANOVA mixed design using SPSS 24. The study reveals: (1) The OLS-CMPBL group has a significant difference in the level of digital literacy skills (sig .0000); (2) the OLS-CMPBL was most effective to improve the skills with gain score 0.207 (low). Learning with the OLS-CMPBL model can be an alternative for policymakers and teachers to solve the problems of digital literacy.